Qualidade do solo em áreas de expansão da cultura soja no Rio Grande do Sul - Goergen, Nádia (2020)
The change in soil quality in areas of agricultural expansion, especially when the native vegetation is converted into pasture and later in crops with soybean cultivation is accompanied by many uncertainties. This change in the agricultural production model may be deteriorating the quality of the soil, depending on physical chemical and biological properties, and this has been a cause for concern. In recent years, studies have started to emerge, but still very incipient based on strategies that seek to integrate these diverse properties, capable of generating soil quality indexes. In this sense, the objectives of this study were (i) to assess changes in physical, chemical and biological soil properties in different crops and soil classes; (ii) determine the impacts of land use change in regions where soybean is expanding; and (iii) verify that the Soil Management Assessment Framework (SMAF) tool is sensitive to detect and quantify changes in soil quality as a function of the different uses evaluated. The tested hypothesis is that the different soil management practices carried out in converting natural environments to agronomic uses manage to maintain soil quality. To this end, the work was carried out in regions of expansion of soybean culture in Rio Grande do Sul. The soil classes evaluated were dystrophic Red Latosol, using native forest soil (MN), cultivated pasture (PA) and soybean under no-tillage (SO), and in distrophic Red Yellow Argisol and typical Ortic Luvisol, both with uses of native field soil (CN), PA and SO. The soil samples were collected in the 0.0–0.10 m layers; 0.10–0.20 m and 0.20–0.30 m for physical and chemical analysis, and in the 0.0–0.10 m layer for biological analysis. In situ, the soil structure was evaluated using the Visual Evaluation of Soil Structure (VESS) methodology. The soil quality was quantified by the SMAF methodology, including the pH, phosphorus (P), potassium (K), soil density (Ds), microbial biomass carbon (CBM) and total organic carbon (COT) properties. The management with PA and SO negatively affected the physical properties of the soil and favored the chemical properties in all evaluated soil uses. The MN showed better soil quality than the other soil uses in the dystrophic Red Latosol. The conversion of CN to PA and SO in the distrophic Red Yellow Argisol and in the typical Ortic Luvisol do not significantly reduce the soil quality, where for the latter, there was an increase in the index for managed systems. The SMAF proved to be capable of detecting changes in soil quality as a result of different managements, being a promising tool for analyzing soil quality in Rio Grande do Sul.